2007
DOI: 10.1002/ajmg.b.30464
|View full text |Cite
|
Sign up to set email alerts
|

Association of the neuronal nicotinic receptor β2 subunit gene (CHRNB2) with subjective responses to alcohol and nicotine

Abstract: Nicotine addiction and alcohol dependence are highly comorbid disorders that are likely to share overlapping genetic components. We have examined two neuronal nicotinic receptor subunit genes (CHRNA4 and CHRNB2) for possible associations with nicotine and alcohol phenotypes, including measures of frequency of use and measures of initial subjective response in the period shortly after first using the drugs. The subjects were 1,068 ethnically diverse young adults participating in ongoing longitudinal studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 58 publications
6
115
1
6
Order By: Relevance
“…A study of Korean adult alcoholics revealed an association with CHRNA4 , in addition to significant effects of several other candidate genes (Kim et al, 2004). Focusing on the subjective responses to nicotine and alcohol, Ehringer et al (2007) showed a modest CHRNA4 association with alcohol (but not nicotine) in Caucasian adolescents recruited from substance use treatment centers, the criminal justice system, and community-based studies. Subsequent studies from this research group using this cohort have gone on to reveal modest associations between CHRNA4 and adolescent nicotine dependence (Kamens et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…A study of Korean adult alcoholics revealed an association with CHRNA4 , in addition to significant effects of several other candidate genes (Kim et al, 2004). Focusing on the subjective responses to nicotine and alcohol, Ehringer et al (2007) showed a modest CHRNA4 association with alcohol (but not nicotine) in Caucasian adolescents recruited from substance use treatment centers, the criminal justice system, and community-based studies. Subsequent studies from this research group using this cohort have gone on to reveal modest associations between CHRNA4 and adolescent nicotine dependence (Kamens et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Two studies have reported associations between CHRNA4 haplotypes and smoking-related phenotypes (Feng et al, 2004;Li et al, 2005). Ehringer et al (2007) found an association between SNPs in the CHRNA4 gene and current smoking and between both smoking and alcohol subjective response phenotypes and a SNP in the CHRNB2 gene. The CHRNB3 and CHRNB5 genes have also emerged as strong candidates for nicotine dependence in two recent reports of a genome wide association and a high-throughput candidate gene survey (Bierut et al, 2007;Saccone et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The CHRNB3 and CHRNB5 genes have also emerged as strong candidates for nicotine dependence in two recent reports of a genome wide association and a high-throughput candidate gene survey (Bierut et al, 2007;Saccone et al, 2007). Additionally, CHRNB3 has been associated with alcohol abuse in males (Zeiger et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study investigated the relation between CHRNB2 and initial subjective responses to smoking (e.g. feeling dizzy or nauseous after smoking) and identified one SNP (rs2072658) located upstream of the CHRNB2 gene that was associated with an increased response to the negative effects of smoking, whereas another SNP (rs2072660) located in the 3' UTR was associated with a reduced subjective response to the negative effects of smoking [40]. Thus, the results from these studies suggest that polymorphisms in CHRNB2 may also modulate smoking-related behaviors.…”
Section: The β2 Nachr Subunit (Chrnb2)mentioning
confidence: 99%